The Role of Conflict in Economic Decision Making Groups: Some Empirical Results - Bower, Joseph L. (Quarterly Journal of Economics, 1965)
I. Introduction, 263. — II. Developments in normative group decision theory, 264. — III. Questions and an experiment, 267; assumption of a group of rational individuals, 267; two experimental problems: the rational team and the foundation, 268. — IV. The results, 271. — V. Summary and conclusions, 276.